2012
DOI: 10.3329/bjo.v18i2.11983
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser versus blunt dissection tonsillectomy

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…This might relate to thermal tissue damage by the diode laser causing an intense inflammatory reaction, which would trigger a higher degree of pain. The same pattern of post-operative pain after diode laser tonsillectomy was reported by Matin and Chowdhury: they showed that pain correlated with the production of a thick slough over the tonsil beds 25 …”
Section: Discussionsupporting
confidence: 74%
“…This might relate to thermal tissue damage by the diode laser causing an intense inflammatory reaction, which would trigger a higher degree of pain. The same pattern of post-operative pain after diode laser tonsillectomy was reported by Matin and Chowdhury: they showed that pain correlated with the production of a thick slough over the tonsil beds 25 …”
Section: Discussionsupporting
confidence: 74%
“…Postoperative pain should be minimized not just for the patients comfort but also because it may impair swallowing with a risk of dehydration, infection and secondary haemorrhage. Hot electrosurgery and laser tonsillectomy has been reported to cause more severe postoperative pain than conventional blunt dissection technique 18,19 . In our study, we found that children of coblation group experienced mild to moderate pain with maximum on day 2 and no pain on day 8 in comparison to dissection group where children experienced moderate to severe pain with maximum pain on day 4 and mild pain on day 8 .…”
Section: Resultsmentioning
confidence: 99%
“…1 Various methods of tonsillectomy have been practiced over the century aimed at reducing or eliminating intraoperative and postoperative morbidity. 2 Since the first tonsil removal performed by Celsus in 30 BC. 3 Multiple surgical techniques have been described anddiverse instruments have been evolved for this purpose.…”
Section: Introductionmentioning
confidence: 99%